The Merits of New Pollutants and How to Get Them When Patents Are Granted - Grischa Perino (University of Heidelberg, Department of Economics, 2006)
The performance of market based environmental regulation is affected by patents and vice versa. This interaction is studied for a new type of innovation where new technologies reduce emissions of a specific pollutant but at the same time cause a new type of damage. A robust finding is that the efficiency of permits is affected by monopoly pricing of the patent-holding firm. This result carries over to other types of innovation. Taxes are inefficient if technologies produce perfect substitutes and share all scarce inputs. Moreover, the optimal tax on pollution might be negative.
Keywords: Q55; L5; H23; O3; 330; Innovation; Environment; Instrument Choice; Patents; Monopoly Pricing; Umweltpolitik; Umwelttechnik; Patent; Innovation; Monopolistischer Wettbewerb; Umweltökonomik; Theorie